Spatiality and Landscape in National Representations during the Chilean Popular Front, 1983-1941 - Silva, Bárbara (Revista de Historia Social y de las Mentalidades, 2018)
This article explores the construction of national representations during the Chilean Popular Front, focusing on the uses of geographic and spatial references. The Popular Front was a political project opposed to the traditional ruling oligarchy, but together with that idea of novelty, which strengthened the popular notions of national identity, other elements remained, that addressed to national cohesion. National geography and landscapes were among those referents. With this perspective, the paper questions the objective character of the territory, analyzes the role that landscape can play in nation-building processes, and how communities subjectively appropriate and give social meaning to spatiality.
Keywords: Nation Building; Spatial Identities; National Landscapes; Chilean Popular Front